A retrospective cohort study of pregnancy outcomes during the pandemic period of the SARS‐CoV‐2 omicron variant: A single center's experience. Issue 2 (4th July 2022) - Floyd, Ruairí; Hunter, Samuel; Murphy, Niamh; Lindow, Stephen W.; O'Connell, Michael P.
Synopsis: Our retrospective review revealed that antenatal infection with the Omicron variant is associated with minimal symptoms in vaccinated patients, minimal medical intervention, and good obstetric outcomes.